An Efficient Dynamic Round Robin algorithm for CPU scheduling - Farooq, Muhammad Umar; Shakoor, Aamna; Siddique, Abu Bakar (2017 International Conference on Communication, Computing and Digital Systems (C-CODE), 2017)
The efficiency of embedded systems mainly depends on the process scheduling policy of operating systems running on them. Better scheduling algorithms make a system fast using less resources for small time. Out of some important scheduling algorithms, Round Robin algorithm is much efficient. But its efficiency fairly depends on choosen time quantum. In this paper, we have developed an efficient Round Robin algorithm using Dynamic Time Quantum. Some such systems have already been developed but they take advantage of other algorithms and their running time is much higher due to sorting of processes which is practically impossible. So, our goal is to reduce running time of an algorithm along with efficiency constraints such as context switches, average waiting and turnaround times. Lower the context switches, average waiting and turnaround times; higher the efficiency of an operating system and thus better embedded system. In the last section of this paper, we will present a comparison of our system with previously developed algorithms.